ANGULAR PREGNANCY: AN ECCENTRIC IMPLANTATION WITHIN UTERINE CAVITY - Mustafa, Nilofar; Mushtaq, Qurratulain; shah, Syed Muhammad Bilal (Journal of Ayub Medical College Abbottabad, 2021)
Angular ectopic is a rare form of ectopic pregnancy which is diagnosed as intrauterine pregnancy on ultrasound but may rupture in second trimester leading to maternal mortality. We present a case of a 32-year-old primigravida who presented at 18 weeks gestation to the emergency department of national hospital Lahore with complaint of dizziness, sweating and epigastric pain for one hour. She had an episode of diarrhoea and vomiting at hospital followed by rapidly increased abdominal distension and signs of hypovolemic shock. Urgent ultrasound suggested rupture of posterior uterine wall and massive hemoperitoneum. An urgent laparotomy was done. Uterus was perforated by pregnancy posteriorly. baby was inside the sac and alive. But died soon after birth. Uterus was repaired in two layers. Stepwise devascularization of uterus was done due to continuous bleeding. 6 units whole blood 6 FFP were transfused. The abnormal location of this pregnancy makes it antenatal diagnosis difficult. A high index of suspicion is needed in pregnant women presenting in shock even when intrauterine location of pregnancy is diagnosed in first trimester.